" Compositional characteristics and industrial assessment of sedimentary clay bodies in part of eastern Dahomey Basin, southwestern Nigeria " (2005)
"Clay bodies occur as lenses and interbeds within the predominantly shaley Akinbo Formation in the eastern Dahomey Basin. They are greenish to grayish, plastic, and in some places contain concretions. In order to assess their sedimentological significance as well as evaluate their potential as industrial raw materials, representative outcrop arid borehole samples .were subjected to mineralogical, chemical and physical characterization. Mineralogical determination by X-ray diffraction (XRD) method, indicates kaolinite as the major clay mineral, with a range of 32.86-58.33%. Other constituents are illite (4.95%), smectite (2.87-14.29%) and palygorskite (2.87%). The non-clay minerals are quartz, K-feldspar, micas and graphite. In terms of chemical composition, the clay bodies. are characterised by the following; Si02 (52.96-55.84%), Al2O3 (16.22-17.74%) Fe203 (7.13-10.35%); CaO (4.65-7.95%)-; MgO (2.26-3.98%) while Na20, K2O, MnO, Ti02 and P2Os have individual values < 1%. The relatively high CaO reflect some contribution from the limestone bed underlying this formation. The clay specimens generally display colour ranging from grayish in fresh, to brownish-red on firing. Corresponding values of physical parameters include linear shrinkage (3.75-7.50%), plastic limit (23- 31%), liquid limit (48-56%), plasticity index (21-30%) and water absorption capacity (5.80-11.90%). The average silica sesquioxide and alumina-iron oxide ratios are respectively 2.17 and 2.08. These values are within the range suitable for clays or shales to be used in the manufacture of good quality cement. The clays have high silica content and are relatively rich in fluxing elements such as Ca and Mg, and could be utilized in the manufacture of domestic and sanitary earth wares. The high plasticity as reflected by the values of the relevant physical indices, and the general fineness qualify the clays to be useful as fillers or coating materials in paper and paint industries. They could also be useful in the production of construction bricks, ceramics, and with beneficiation, the quality might improve for other applications. "